2023
DOI: 10.3389/fpsyg.2023.1062830
|View full text |Cite
|
Sign up to set email alerts
|

Balancing benefits and risks in lung cancer therapies: patient preferences for lung cancer treatment alternatives

Abstract: BackgroundIn the treatment of Non-Small Cell Lung Cancer (NSCLC) the combination of Immuno- Oncotherapy (IO) and chemotherapy (CT) has been found to be superior to IO or CT alone for patients’ survival. Patients and clinicians are confronted with a preference sensitive choice between a more aggressive treatment with a greater negative effect on quality of life versus alternatives that are less effective but have fewer side effects.ObjectivesThe aims of this study were to: (a) quantify patients’ preferences for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Our study is concordant with previous findings that the likelihood of undergoing GCT decreases with disease progression in NSCLC cases, was higher in stage I–II NSCLC than in stage III–IV NSCLC, this may be related to more direct patient selection and increased expectations of treatment outcomes. The majority of patients who did not undergo GCT presented with advanced disease, with quality of life (QOL) rather than survival likely to be an important consideration, and a previous study reported that patient preference for treatment was the most common reason for not seeking expert advice ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is concordant with previous findings that the likelihood of undergoing GCT decreases with disease progression in NSCLC cases, was higher in stage I–II NSCLC than in stage III–IV NSCLC, this may be related to more direct patient selection and increased expectations of treatment outcomes. The majority of patients who did not undergo GCT presented with advanced disease, with quality of life (QOL) rather than survival likely to be an important consideration, and a previous study reported that patient preference for treatment was the most common reason for not seeking expert advice ( 48 ).…”
Section: Discussionmentioning
confidence: 99%